Biological Fitness, Resistance Characterization, Resistance Risk Assessment And Evaluation Of Selected Baits On Fipronil- And Indoxacarb Bait-Selected Strains Of The German Cockroach, Blattella Germanica (Linnaeus) (Dictyoptera: Blattellidae) - Ang, Ling Hui (2013)
This study focuses on insecticide resistance in the German cockroach. Several aspects were investigated, including biological fitness, insecticide toxicity, cross-resistance potential, resistance development and risk assessment, resistance mechanisms involved as well as bait performance evaluation. Selected biological fitness were compared between insecticide-resistant and insecticide-susceptible German cockroaches. Most resistant strains showed no significant difference in nymphal development period, preoviposition period, incubation period, nymphal and oothecal production, ootheca measurements, nymphal survivorship, and adult longevity compared to those of the susceptible strain. These results indicate that the resistant allele is not deleterious in aspect of fitness.